Simple Mail Box Design of Dual Band Microstrip Patch Antenna for Wireless LAN Communications - K. Thana Pakkiam; K. Baskaran; J. S. Mandeep (Bulletin of Electrical Engineering and Informatics, 2018)
In this paper, a simple mail box design of a dual band microstrip patch antenna, is proposed, designed, fabricated and measured for wireless LAN communications. The proposed antenna is designed using the TLC 30 (TACONIC) substrate, with a relative permittivity of 4.3 and substrate height of 1.6mm. It is designed to operate at 2.44 GHz and 5. 30 GHz respectively. The proposed antenna is the size of 31mm x 34mm x1.6mm and is incited by a 50 Ω micro strip feed line. The characteristics of the antenna are designed and the performance of the modelled antenna is evaluated using CST Microwave Studio. The return loss, radiation patterns and peak antenna gain of 6.5 dBi for frequency 2.44 GHz and 6.2 dBi for 5.30 GHz is separately and successfully plotted. The fabricated prototype exhibits an agreement between the measured and simulated return loss.